The Effects of Two Different Types of Incentive Spirometry Applied Postoperatively on Vital Signs, Pain and Fatigue Status of Patients Undergoing Urological Surgery. - Aydın, Hümeyra; Ataç, Amine; Akıl Ağdere, Selin; Artuk, İlker; Öztürk, Metin İshak (Lokman Hekim Health Sciences, 2025)
Introduction: It is important for patients to be included in a pulmonary rehabilitation program before and after surgery to prevent postoperative complications. Incentive spirometry is designed to mimic maximum deep inspiration and encourages the patient to take long, deep, slow breaths that increase lung volume. The aim of this study is to investigate the effects of two different types of incentive spirometry applied postoperatively on vital signs, pain, fatigue and dyspnea of patients undergoing urological surgery. Methods: 159 patients who underwent urological surgery were randomly assigned to the Volume-Oriented Incentive Spirometry Group (VISGr) (n=53), Flow-Oriented Incentive Spirometry Group (FISGr) (n=53) and Standard Respiratory Exercise Group (SREGr) (n=53). After surgery, 10 breathing exercises and 10 incentive spirometry were performed 4 times. Participants' vital values, fatigue, pain and dyspnea parameters were evaluated at certain times preoperative stage, postoperative stage, before exercise (BE) and after exercise (AE). Results: As a result of the evaluations, a significant difference was found between the groups in systolic blood pressure values before and after the fourth exercise session and in postoperative Borg Leg fatigue and visual analog scale general fatigue values after the last exercise session. In the intra-group evaluation, a significant improvement was found in pain values in all three groups. Discussion and Conclusion: Incentive spirometry, which is used to prevent adverse effects on lung volumes that may occur in surgical situations, can be considered as an economical method of additional sort to provide symptom control, regardless of its type.